Problems and solutions of rice consumption pattern in West Java - Mochammad Fikry Pratama; Syaima Rima Saputri; Lydia Nursyamsi; Ika Nur Fariha; Nadya Myrilla; Lutfi Dwi Mulya; Yooce Yustiana (School of Life Sciences and Technology, Institut Teknologi Bandung, 2019)
West Java is one of the provinces in Indonesia where the staple food is rice. The high ability of rice provisioning and the government's encouragement through the policy of uniformed staple food gave a negative impact on rice consumption patterns of West Java population. This pattern of consumption will become a problem when faced with the fact that the rice production area has declined (0.67% per year) and the population increased (1.41% per year). Based on projection of production and needs of rice, it is predicted that West Java will experience shortages in 2040. Therefore this research aimed to discuss efforts to prevent rice dependency problem. The entire study used case study approach. By using secondary data, basically the government has made many efforts to resolve the problems. In fact, there are some obstacles and the mismatch on results. Therefore the alternative solutions are: a). diversification efforts with rice commodity substitution based on geographical location, b). socialization, c). rice price policy, and c). improved education and economics.